Pengaruh Corporate Social Responsibility (Csr) Dan Green Banking Terhadap Kinerja Perusahaan Pada Perusahaan Sektor Perbankan Yang Terdaftar Di Bei - Feranti Feranti; Riri Mayliza (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
A company is required to prioritize its surrounding environment to ensure that its operations do not cause adverse effects on nature and the surrounding community. This study aims to examine the impact of Corporate Social Responsibility (CSR) and Green Banking on corporate performance. The sampling technique used in this study is purposive sampling based on predetermined criteria. The research sample consists of banking companies listed on the Indonesia Stock Exchange. Of the 47 banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period, a final sample of 16 companies was selected. Panel data regression analysis was employed as the analytical method. The results of the study indicate that: (1) Corporate Social Responsibility has a positive and significant effect on corporate performance, and (2) Green Banking does not have a significant effect on corporate performance.